A Review of State Guidelines for Elective Orthopaedic Procedures During the COVID-19 Outbreak. (3rd June 2020) - Sarac, Nikolas J.; Sarac, Benjamin A.; Schoenbrunner, Anna R.; Janis, Jeffrey E.; Harrison, Ryan K.; Phieffer, Laura S.; Quatman, Carmen E.; Ly, Thuan V.
Abstract : Background: The SARS-CoV-2 (COVID-19) pandemic has resulted in widespread cancellation of elective orthopaedic procedures. The guidance coming from multiple sources frequently has been difficult to assimilate as well as dynamic, with constantly changing standards. We seek to communicate the current guidelines published by each state, to discuss the impact of these guidelines on orthopaedic surgery, and to provide the general framework used to determine which procedures have been postponed at our institution. Methods: An internet search was used to identify published state guidelines regarding the cancellation of elective procedures, with a publication cutoff of March 24, 2020, 5:00 P.M. Eastern Daylight Time. Data collected included the number of states providing guidance to cancel elective procedures and which states provided specific guidance in determining which procedures should continue being performed as well as to orthopaedic-specific guidance. Results: Thirty states published guidance regarding the discontinuation of elective procedures, and 16 states provided a definition of "elective" procedures or specific guidance for determining which procedures should continue to be performed. Only 5 states provided guidelines specifically mentioning orthopaedic surgery; of those, 4 states explicitly allowed for trauma-related procedures and 4 states provided guidance against performing arthroplasty. Ten states provided guidelines allowing for the continuation of oncological procedures. Conclusions: Few states have published guidelines specific to orthopaedic surgery during the COVID-19 outbreak, leaving hospital systems and surgeons with the responsibility of balancing the benefits of surgery with the risks to public health.